GOALS AND TASKS OF DEVELOPMENT OF LOCAL STATE AUTHORITIES IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
The article discusses the modernization process of local self-government in Uzbekistan during independence. At the same time, the author provides information on several proposals to attract innovations to the industry and talks about plans to reform local authorities.